Maximal lactate steady state and the upper boundary of heavy intensity domain in trained cyclists - Camila Coelho Greco; Benedito Sergio Denadai; Fabrizio Caputo; Renato Aparecido Corrêa Caritá; Jailton Gregório Pelarigo; Mariana Rosada de Souza; Luis Fabiano Barbosa (Revista Brasileira de Cineantropometria e Desempenho Humano, 2009)
The objective of this study was to determine the validity of maximum lactate steady state (MLSS) for the identification of the upper limit of the heavy-intensity domain in well-trained cyclists. Fourteen male cyclists (25.5 ± 4.4 years, 69.5 ± 7.8 kg, 175.8 ± 7.5 cm) underwent the following tests on different days: incremental exercise test until exhaustion to determine peak oxygen uptake (VO2peak), and 2 to 4 constant submaximal load tests to determine MLSS. VO2 obtained in the 30th min was significantly higher than that obtained in the 3rd min of exercise performed at 100% MLSS (3379.3 ± 250.1 vs. 3496.7 ± 280.2 ml/min, p<0.05) and 105% MLSS (3439.5 ± 289.3 vs. 3545.5 ± 303.2 ml/min, p<0.05). VO2 obtained in the 30th min of exercise performed at 100% and 105% MLSS was significantly lower than VO2peak (3978.6 ± 296.2 ml/min, p>0.05). These results suggest that during heavy exercise (MLSS) VO2 does not present stability when values obtained around the 3rd minute of exercise are used as reference. MLSS does not seem to be the upper limit of the heavy-intensity domain in trained subjects since VO2peak is not reached by the end of 30 min of exercise when exercise is performed above this intensity (~ 5%).